Prominent muscle involvement in a familial form of mitochondrial disease due to a COA8 variant - Rimoldi, Martina; Magri, Francesca; Antognozzi, Sara; Ripolone, Michela; Salani, Sabrina; Piga, Daniela; Bertolasi, Letizia; Zanotti, Simona; Ciscato, Patrizia; Fortunato, Francesco; Moggio, Maurizio; Corti, Stefania; et al. (Frontiers in Genetics, 2023)
Isolated mitochondrial respiratory chain Complex IV (Cytochrome c Oxidase or COX) deﬁciency is the second most frequent isolated respiratory chain defect. Causative mutations are mainly identified in structural COX subunits or in proteins involved in the maturation and assembly of the COX holocomplex. We describe an Italian familial case of mitochondrial myopathy due to a variant in the COX assembly factor 8 gene (COA8). Patient 1 is a 52-year-old woman who presented generalized epilepsy and retinitis pigmentosa at 10 years of age. From her early adulthood she complained about cramps and myalgia after exercise, and bilateral hearing loss emerged. Last neurological examination (52 years of age) showed bilateral ptosis, muscle weakness, peripheral neuropathy, mild dysarthria and dysphonia, cognitive impairment. Muscle biopsy had shown the presence of ragged-red fibers. Patient 2 (Patient 1’s sister) is a 53-year-old woman presenting fatigability, myalgia, and hearing loss. Neurological examination showed ptosis and muscle weakness. Muscle biopsy displayed a diffuse reduction of COX activity staining and ragged-red fibers. Both sisters presented secondary amenorrhea. After ruling out mtDNA mutations, WES analysis identified the novel homozygous COA8 defect c.170_173dupGACC, p.(Pro59fs) in the probands. Loss-of-function COA8 mutations have been associated with cavitating leukoencephalopathy with COX deﬁciency in 9 reported individuals. Disease course shows an early-onset rapid clinical deterioration, aﬀecting both cognitive and motor functions over months, followed by stabilization and slow improvement over several years. Our findings expand the clinical spectrum of COA8-related disease. We confirm the benign course of this rare disorder, highlighting its (intrafamilial) clinical variability.